HALAL CERTIFICATION FOR MSMEs: PROTECTION OF THE FIVE BASIC ASPECTS OF LIFE (AD-DHARURIYYAH AL-KHAMSAH) AND STRATEGIES TO STRENGTHEN ITS IMPLEMENTATION - Nopriansyah, Waldi; Muntazhor, Ahmad Widad; Chantika, Zalvira; Choiriyah, Choiriyah; Meriyati, Meriyati (istinbath, 2025)
This study investigates the persistently low compliance of Micro, Small, and Medium Enterprises (MSMEs) with halal certification, despite its critical role in safeguarding the five essential objectives of Islamic law (ad-dharuriyyah al-khamsah): religion (dīn), life (nafs), intellect (‘aql), lineage (nasl), and property (māl). Employing a qualitative research design, this study utilizes a descriptive-analytical approach supported by thematic content analysis. Data were collected through a systematic literature review, including primary Islamic sources (Qur’an, Hadis, and classical jurisprudence) and relevant secondary literature (peer-reviewed journals, regulations, and government reports). The findings were categorized based on the maqāṣid al-shari'ah framework to ensure a structured and normative analysis. The results reveal that halal certification serves as a multidimensional protection mechanism, with the preservation of life (ḥifẓ al-nafs) identified as the most urgent priority. This emphasis stems from product consumption's direct psychological and ethical implications on human well-being. By elevating ḥifẓ al-nafs above traditional priorities such as ḥifẓ al-dīn, the study offers a contextual reinterpretation aligned with contemporary public health and ethical standards. Moreover, this research fills a notable gap in the literature by explicitly linking halal certification to the comprehensive structure of ad-dharuriyyah al-khamsah, a dimension often overlooked in previous studies. Policy recommendations include financial incentives, awareness campaigns, streamlined regulations, and stakeholder collaboration, highlighting the dual role of halal certification as both a religious obligation and a vehicle for public welfare.